Microfoundations of Dynamic Capability dalam Mendukung Keberlanjutan Usaha Keluarga di Era Transformasi Digital: A Systematic Literature Review: Penelitian - Rahmah Khairunnisa B; Andy Eko Aprianto; Santy Dewi Muh Lutfi; St. Nurhayati Azis (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Digital transformation has compelled family businesses to strengthen their adaptive capabilities to ensure long-term sustainability. One of the most prominent perspectives explaining organizational adaptability is dynamic capability, which is built upon microfoundations encompassing individual capabilities, organizational processes, and learning mechanisms. This study aims to identify, analyze, and synthesize the existing literature on the role of microfoundations of dynamic capability in supporting family business sustainability in the digital transformation era. A Systematic Literature Review (SLR) following the PRISMA guidelines was employed. Articles were retrieved from the Scopus and Web of Science databases using predefined inclusion criteria, including English-language journal articles published within the last five years. A total of 15 eligible articles were analyzed using content analysis through coding, categorization, and thematic synthesis. The findings reveal that microfoundations of dynamic capability play a crucial role in enhancing family firms' abilities to sense opportunities, seize emerging opportunities, and transform organizational resources in response to environmental changes. The synthesis identifies six major dimensions of microfoundations: managerial skills and knowledge, social networks and collaboration, product and process innovation, responsiveness to market changes, adaptive policies and strategies, and digital technology adoption. This study contributes to the literature by providing a comprehensive synthesis of microfoundations of dynamic capability and offers practical insights for strengthening adaptive strategies to enhance the sustainability of family businesses in the era of digital transformation.